Estudio de factibilidad para la creación de una empresa productora y comercializadora de bebidas hidratantes con sabor a hierbas medicinales, en la ciudad de Loja - Medina Zhapa, Víctor Vinicio (2016)
This work was developed in the city of Loja, in order to perform a " Feasibility Study for the establishment of a company that produces and markets sports drinks flavored with herbs , in the city of Loja " with the aim of providing a healthy quality product at affordable prices to meet the needs of the citizenry power . The study begins with the wording of the Summary, Introduction, this followed the Literature Review, which contains all the terms used in this project, then the detailed methodology was performed. Here are the results of the project were the same as obtained by the application of tools such as surveys and interviews in addition to the collaboration of several people who helped to get the necessary information as consumers, vendors , suppliers, and others is presented , that it helped tremendously to the development stage of the project. It begins with the study of market in which market segmentation for which we use the Economically Active Population PEA, Loja city of 84,712 people that is performed, this information allowed us to determine the number of surveys that are 382 which were applied in the urban area of the city at strategic locations. Then the required demands of the project are determined, the potential demand representing 100 % of the people if they consume drinks due to be a necessary item to daily life. Actual demand is composed by 84% of respondents would like to purchase drinks. Tools for effective demand that corresponds to 94% if buy based drinks lemon verbena. Technical Study was designed to establish the necessary processes, such as product engineering , plant size , in which the installed capacity is 100 % and 80% used is set . It was determined that the annual production of beverages, for the first year is 126,720 liters and for the fifth year will have to produce 151,095 liters. Then the engineering project was conducted, the production process, in which the steps are as accomplished, to the finished product, the engineer of the plant where the macro and micro localization is determined so that the company will be located in Loja, at the Citadel the Valley , in the streets, Jose Valdivieso, between Av and Av Salvador Bustamante Celi Dario Eguiguren . In addition to Conduct a Legal Management Study which the mission, vision and objectives of the Company is defined as well as the corporate organizational structure and function on which develops the corresponding charts and therefore the functions manual also states indicating tasks for each position, the nature of work and the requirements that employees shall exercise such charges . In another development stage of the project Financial Study in which fixed assets are disclosed, deferred assets and working capital or current assets , where they determine that the investment in the project is $ 30.023.82 was performed. The same was financed by an internal source of 20023.82 equivalent to 67 % between 3 partners. And from an external source of $ 10,000.00 equivalent to 33 % will be in the Bank for 5 years at 11 % per annum. In addition, an Operating Budget was held that for the first year is $ 61,689.80, it helps to determine the unit cost is 0.49 cents. While the retail price is 0.56 cents. With a profit margin of 15%, generating sales of $ 70943.27 all in the first year. With this an analysis and classification of costs for each the first and fifth years of project life, with these data was made the point of balance for the first year is $ 55,437.91 with respect to sales and 78.14 % was produced with relation to the installed capacity for the 5th. Year is $ 75,154.57 with respect to sales and 78.08 % in relation to the installed capacity, and the State of Income. Finally the financial evaluation was performed using different indicators such as cash flow than for the first year is $ 9735.42 Net Present Value NPV is $ 6608.28 which shows that the project is profitable, the Recovery Period was performed capital which describes the investment is recovered in 4 years 1 month, 27 days. Indicator Value Through Profit Cost is determined that the following result is deducting $ 1.15 cents for every dollar invested is expected a profit of $ 0.15 cents, the Internal Rate of Return is the 25.82 % and sensitivity Analysis indicates that for this project, the sensitivity values are lower than 1, therefore does not affect changes in project costs and revenues increased by 0.77% and decreased in 0.67% respectively. Finally exposed to the conclusions and recommendations which comes after finishing the Thesis Project. So the implementation of the same is recommended considering the results. Major reference sources used to develop this work is presented in some of the literature. Format of the survey and interview used for the collection of information is presented in the Annexes. Finally the index by which readers can follow and find faster the specific item you are looking for in the project.